2022
DOI: 10.3390/coatings13010034
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Structural, Optical and Electrical Properties of Zinc Oxide Nanostructures by Zirconium Doping

Abstract: Owing to its low resistivity, high transmittance, and tunable optical band gap, ZnO is of great interest for optoelectronic applications. Herein, the sol–gel technique was used to synthesize un-doped and zirconium-doped zinc oxide (ZZO) nanostructures with different concentrations of Zirconium (Zr). X-ray diffraction (XRD), scanning electron microscope (SEM), Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), UV-Vis spectroscopy, and photoluminescence (PL) measurements were used to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Additionally, Rajkumar et al [37] observed a degradation in (002) intensity with increasing Zr content in sol-gel-deposited Zr:ZnO films. In contrast, Khan et al [38] did not observe any changes in diffraction peak intensities with increasing Zr content. These discrepancies may be attributed to variations in deposition parameters and techniques utilized across different studies.…”
Section: Structural Propertiesmentioning
confidence: 76%
See 1 more Smart Citation
“…Additionally, Rajkumar et al [37] observed a degradation in (002) intensity with increasing Zr content in sol-gel-deposited Zr:ZnO films. In contrast, Khan et al [38] did not observe any changes in diffraction peak intensities with increasing Zr content. These discrepancies may be attributed to variations in deposition parameters and techniques utilized across different studies.…”
Section: Structural Propertiesmentioning
confidence: 76%
“…The incorporation of Zr into the ZnO lattice offers a promising avenue for tailoring and enhancing the properties of thin films for various applications. One key advantage of Zr doping is the potential to improve the electrical conductivity and carrier concentration of ZnO thin films [30], making them more suitable for electronic and optoelectronic devices [31]. Additionally, Zr doping can help optimize material properties such as bandgap energy, optical transparency [31], and structural stability, enabling the development of highperformance thin film devices [32] with enhanced functionality and reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Under the irradiation excitation, charge transfers from O 2 2p and Bi 6s orbitals to the conduction band of Bi, which is a 6p orbital, and the peak at 465 nm forms due to the recombination of free excitons after the de-excitation. , The band edge emission peak at 456 nm for pure α-Bi 2 O 3 nanoparticles (denoted as * in Figure ) shifted toward shorter wavelengths with increasing concentration of Zn 2+ ion in α-Bi 2 O 3 nanoparticles; e.g., for ZBO–D it occurs at 441 nm. The shifting of band edge emission peak toward the lower wavelength with increasing concentration of Zn 2+ is due to the improvement in energy of the band-to-band recombination according to the Burstein–Moss effect . In Zn 2+ -doped α-Bi 2 O 3 nanoparticles, the other three peaks were also recorded.…”
Section: Resultsmentioning
confidence: 96%
“…To investigate the effect of Zn 2+ ion on the electrical properties of α-Bi 2 O 3 nanoparticles, commonly used Hall measurements (Van der Pauw technique) were carried out to measure the carrier concentration, carrier type, resistivity, conductivity, and mobility of the fabricated nanoparticles . All of the synthesized nanoparticles showed n-type conductivity, and it was also observed that the conductivity and carrier mobility increase from 5.91 × 10 –6 S cm –1 for ZBO-A to 2.19 × 10 –5 S cm –1 for ZBO–D and 0.611 cm 2 /V·s for ZBO-A to 6.89 cm 2 /V·s for ZBO–D, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation